Noninvasive management of soft tissue disorders of the shoulder: A clinical practice guideline from the Ontario Protocol for Traffic Injury Management (OPTIMa) collaboration. (17th May 2021) - Yu, Hainan; Côté, Pierre; Wong, Jessica J.; Shearer, Heather M.; Mior, Silvano; Cancelliere, Carol; Randhawa, Kristi; Ameis, Arthur; Carroll, Linda J.; Nordin, Margareta; Varatharajan, Sharanya; Sutton, Deborah; et al.
Abstract: Objectives: Objective of this study is to develop an evidence‐based guideline for the noninvasive management of soft tissue disorders of the shoulder (shoulder pain), excluding major pathology. Methods: This guideline is based on high‐quality evidence from seven systematic reviews. Multidisciplinary experts considered the evidence of effectiveness, safety, cost‐effectiveness, societal and ethical values, and patient experiences when formulating recommendations. Target audience is clinicians; target population is adults with shoulder pain. Results: When managing patients with shoulder pain, clinicians should (a) rule out major structural or other pathologies as the cause of shoulder pain and reassure patients about the benign and self‐limited nature of most soft tissue shoulder pain; (b) develop a care plan in partnership with the patient; (c) for shoulder pain of any duration, consider low‐level laser therapy; multimodal care (heat/cold, joint mobilization, and range of motion exercise); cervicothoracic spine manipulation and mobilization for shoulder pain when associated pain or restricted movement of the cervicothoracic spine; or thoracic spine manipulation; (d) for shoulder pain >3‐month duration, consider stretching and/or strengthening exercises; laser acupuncture; or general physician care (information, advice, and pharmacological pain management if necessary); (e) for shoulder pain with calcific tendinitis on imaging, consider shock‐wave therapy; (f) for shoulder pain of any duration, do not offer ultrasound; taping; interferential current therapy; diacutaneous fibrolysis; soft tissue massage; or cervicothoracic spine manipulation and mobilization as an adjunct to exercise (i.e., range of motion, strengthening and stretching exercise) for pain between the neck and the elbow at rest or during movement of the arm; (g) for shoulder pain >3‐month duration, do not offer shock‐wave therapy; and (h) should reassess the patient's status at each visit for worsening of symptoms or new physical, mental, or psychological symptoms, or satisfactory recovery. Conclusions: Our evidence‐based guideline provides recommendations for non‐invasive management of shoulder pain. The impact of the guideline in clinical practice requires further evaluation. Significance: Shoulder pain of any duration can be effectively treated with laser therapy, multimodal care (i.e., heat/cold, joint mobilization, range of motion exercise), or cervicothoracic manipulation and mobilization. Shoulder pain (>3 months) can be effectively treated with exercises, laser acupuncture, or general physician care (information, advice, and pharmacological pain management if necessary).